3″-Hydroxymethyl-butyrolactone II from Aspergillus sp. Issue 14 (17th July 2020) - Chen, Gang; An, Xiao; Wang, Haifeng; Pei, Yuehu
Abstract: In continuation of the search for new compounds from the terrestrial fungus Aspergillus sp., one new butyrolactone, 3″ -hydroxymethyl-butyrolactone II (1 ) was isolated. The chemical structure of 1 was confirmed by extensive 1D and 2D NMR and HR-ESI mass data analysis, and by comparison with literature data. The absolute configuration was also determined by ECD calculations. Graphical Abstract: